ANTIMICROBIAL ACTIVITY AND PHYTOCONSTITUENTS SCREENING OF NOXIOUS INVASIVE ALIEN PLANTS, AGERATINA ADENOPHORA AND CHROMOLAENA ODORATA FROM MIZORAM, A PART OF INDO-BURMA BIODIVERSITY HOTSPOT IN INDIA - Rabishankar Sengupta; Arnab Kundu; Bikram Dhara; Arup Kumar Mitra; Sudhansu Sekhar Dash (Exploratory Animal and Medical Research, 2023)
Ageratina adenophora and Chromolaena odorata belonging to the family Asteraceae are the two most noxious invasive alien plant species in the natural forests of Mizoram, a part of the Indo-Burma biodiversity hotspot. These two noxious invasive species should either be controlled by eradication or managed by exploiting them as a resource for bioprospecting like antimicrobial medicines. The present study has explored the two abundantly available invasive species, for bioprospecting and investigating their antimicrobial potential. The obtained results revealed the presence of varying amounts of flavonoids, steroids, tannins, and alkaloids in the polar and non-polar solvent extracts of A. adenophora and C. odorata. The methanol extract of A. adenophora revealed promising antifungal activity against the test plant pathogenic fungi whereas petroleum ether extract of A. adenophora and C. odorata exhibited significant antibacterial potential against both Gram-positive and Gram-negative test bacteria. The results also revealed the solvent extracts of the studied invasive alien plants exhibited almost similar or more effectiveness with that of commonly used synthetic antifungals like Bavistin and broad-spectrum antibiotics like Gentamicin. Investigating the minimum inhibitory concentration of the plant extracts revealed their effectiveness even at minor concentrations. Therefore, the antimicrobial property of these two noxious invasive alien plant species can be recognized as a beneficial resource for medicinal as well as economic purposes for antibacterial and antifungal materials.